A comparative metabolome and proteome analysis to elucidate disease resistance in hot water treated Carica papaya L. cv. Eksotika II / Matthew Raj Alias - Matthew Raj , Alias (2024)
The metabolome and proteome analyses are powerful research techniques utilized to understand the molecular alterations in metabolic and protein profiles of organisms in response to environmental factors. This study uses these methods to investigate the differences in disease resistance between hot water-treated and untreated papaya fruit. The primary objectives are to uncover the molecular pathways involved in disease resistance and identify potential biomarkers of resistance in papaya. Proteome analysis aims to study the impact of environmental factors on protein expression patterns in organisms. In the context of papaya, this analysis helps determine changes in the expression of disease-fighting proteins in hot water-treated fruit. Examples of such proteins include chitinases and pathogenesis-related (PR) proteins. Metabolome analysis focuses on investigating alterations in the metabolic profiles of organisms. In this study, changes in metabolite levels, including sugars, organic acids, and phytohormones, in hot water-treated papaya are assessed. Metabolites are known to play a role in disease resistance. Combining the findings from proteome and metabolome analyses provides a better understanding of the molecular changes associated with disease resistance in hot water-treated papaya. This information can be applied to enhance disease resistance through strategies such as selecting appropriate cultivars or optimizing hot water treatment protocols. In conclusion, comparing metabolome and proteome analyses is an effective approach for investigating the molecular basis of disease resistance in hot water-treated papaya. This knowledge can provide crucial insights into the molecular pathways underlying disease resistance and be utilized to develop strategies for enhancing papaya's resistance to diseases.